Insects as sustainable food ingredients : production, processing and food applications - Dossey, Aaron T.; Morales-Ramos, Juan A.; Rojas, M. Guadalupe (London, United Kingdom : Academic Press is an imprint of Elsevier, 2016)
Insects as Sustainable Food Ingredients: Production, Processing and Food Applications describes how insects can be mass produced and incorporated into our food supply at an industrial and cost-effective scale, providing valuable guidance on how to build the insect-based agriculture and the food and biomaterial industry. Editor Aaron Dossey, a pioneer in the processing of insects for human consumption, brings together a team of international experts who effectively summarize the current state-of-the-art, providing helpful recommendations on which readers can build companies, products, and research programs. Researchers, entrepreneurs, farmers, policymakers, and anyone interested in insect mass production and the industrial use of insects will benefit from the content in this comprehensive reference. The book contains all the information a basic practitioner in the field needs, making this a useful resource for those writing a grant, a research or review article, a press article, or news clip, or for those deciding how to enter the world of insect based food ingredients.
Chapter 1 -- Introduction to Edible Insects Chapter 2 -- History and Cultural Use of Insects Chapter 3 -- Nutrient Content and Health Benefits of Consuming Insects Chapter 4 -- Insect Farming: Efficieny and Impacts on Environment and Family Livelihood Compared with Livestock and Crops or Insect Sustainability Chapter 5 -- Modern Insect Based Food Industry Chapter 6 -- Insect Mass Production Technologies Chapter 7 -- Food Safety and Regulatory Concerns Chapter 8 -- Microbiology Concepts (New chapter title: Ensuring Food Safety in Insect Based Foods: Microbiological and Other Foodborne Hazards) Chapter 9 -- Insects and Their Connection to Food Allergy Chapter 10 -- Brief Summary of Insect Use as an Industrial Animal Feed/Feed Ingredient.
Online resource; title from PDF title page (SpringerLink, viewed July 8, 2016).
Includes bibliographical references and index.
Keywords: Edible insects; COOKING -- General; Edible insects; Essbare Kleinsttiere; Electronic book; Electronic books